(untitled) (Journal of Business Management and Accounting, 2020)
Small and Medium Enterprises (SMEs) are aware of the need to implement proper supply chain management practices, especially to maintain good relationships with their suppliers. Previous studies indicated that a close relationship between SME owner-managers and suppliers can avail various benefits, such as operations and performance improvement, smooth delivery of goods and services to final destinations, and better negotiation of price and delivery schedule. Thus, this paper presents an understanding of the relationship between an SME in the food industry and its suppliers. By employing the Social Exchange Theory (SET) as the underlying theory, this study highlighted the importance of SMEs in managing relationships with suppliers. This study also revealed the roles that factors, such as trust, communication, commitment, and bargaining power, play in the SME-supplier relationship. By employing qualitative methodology and single case study method, this study indicated that this SME is aware that maintaining a good relationship with suppliers can lead to the survival of the business for a longer period of time, and enable them to benefit in terms of cost, quality, and services in the future. Among all factors, loyalty under the commitment factor is considered to be not unduly important to maintain the relationship with the suppliers by the SME owner-manager. However, trust and communication are the most crucial factors to maintain this relationship.